Perancangan Prototype Website sebagai Media Informasi Firdaus Amany Psychological Center - Azanisilia; Adya Mulya Prajana (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2023)
Firdaus Amany Psychological Center is an institution providing psychological services that operates in education, development, and organization. Firdaus Amany Psychological Center offers various services, including psychological consultations, training, seminars, workshops, and psychological tests. With the many services provided by the Firdaus Amany Psychological Center, a media is needed to provide information regarding these services, in this case, the media website. This research aims to design a website prototype as a medium that can inform about the services available at the Firdaus Amany Psychological Center. The data collection process in this research was carried out using observation, interviews, questionnaires, and a literature study. The data that has been obtained is then analyzed using SWOT analysis and visual analysis of the comparison matrix, explained in qualitative descriptive terms. It is hoped that the results of the Firdaus Amany Psychological Center website prototype design can help provide information on available services to patients and prospective patients. This website prototype also provides a page that can show the company's credibility so that it can have a good image.